PENGEMBANGAN SISTEM PENUNJANG KEPUTUSAN DISTRIBUSI IMPOR RAW SUGAR - Marimin, Yeni Herdiyeni dan Arief Maulana (Department of Agroindustrial Technology, Bogor Agricultural University, 2005)
ABSTRACTThe main objective of this research is to develop a Decision Support System for raw cane sugar import distribution among the autorized companies in Indonesia. Distribution criteria considered were the manufacturing capacity of each company and the current utilization of the cane sugar processing machine. There were two models of computation used, namely analytical model derived from manufacturing capacity and optimization model through evolution program/algorithm. Verification showed that the suitable parameters of the evolution program consisted of crossover was 0.9, mutation was 0.1, chromosome regeneration was 0.5, population size was 2500 and maximum iteration was 2500. The result of the evolution program was promissing. The result was 99.96% equal with that of the analytical model. The developed system can be used to distribute the raw cane sugar import quota to each authorized company. Keywords : raw cane sugar, decision support system, import quota distribution, evolution program/algorithm